Estimation of the Error in Measuring the Coordinates of Vibrating Objects Using Laser Coordinate Measuring Systems. General Provisions - Fedyaev Vladimir; Lyudogovsky Peter; Komkova Maria (MATEC Web of Conferences, 2021)
The issues of assessing the measurement error using laser coordinate measuring systems (LCMS) of the geometric parameters of vibrating, and also vibrating objects are considered. At the same time, attention is focused on their time-average values. In a number of special cases, calculated relations are given to estimate the average errors in measuring the amplitude and frequency of vibrations of the objects under consideration, their geometric parameters, such as the distance to the laser tracker, coordinates of points on the surface, and other indicators. It is noted that these ratios were obtained for the first time, therefore, in order to increase their reliability, it is possible to introduce them into the corresponding dependences of correcting coefficients and functions.